Healthy lifestyle behaviour among Ghanaian adults in the phase of a health policy change - Dake Fidelia AA; Tagoe Henry A (BMC, 2011)
Abstract Background Many countries have adopted health policies that are targeted at reducing the risk factors for chronic non-communicable diseases. These policies promote a healthy population by encouraging people to adopt healthy lifestyle behaviours. This paper examines healthy lifestyle behaviour among Ghanaian adults by comparing behaviours before and after the introduction of a national health policy. The paper also explores the socio-economic and demographic factors associated with healthy lifestyle behaviour. Method Descriptive, bivariate and multivariate regression techniques were employed on two nationally representative surveys (2003 World Health Survey (Ghana) and 2008 Ghana Demographic and Health Survey) to arrive at the results. Results While the prevalence of some negative lifestyle behaviours like smoking has reduced others like alcohol consumption has increased. Relatively fewer people adhered to consuming the recommended amount of fruit and vegetable servings per day in 2008 compared to 2003. While more females (7.0%) exhibited healthier lifestyles, more males (9.0%) exhibited risky lifestyle behaviours after the introduction of the policy. Conclusion The improvement in healthy lifestyle behaviours among female adult Ghanaians will help promote healthy living and potentially lead to a reduction in the prevalence of obesity among Ghanaian women. The increase in risky lifestyle behaviour among adult male Ghanaians even after the introduction of the health policy could lead to an increase in the risk of non-communicable diseases among men and the resultant burden of disease on them and their families will push more people into poverty.